METHODS AND ADVANCES IN COMPUTER SIMULATION MODELING OF CELLS - Bakaeva Shoira Bakhshilloevna (Western European Studies, 2024)
Computer simulation modeling of cells is a sophisticated methodology that allows researchers to create detailed virtual representations of cellular processes and dynamics. Combining principles of biology, mathematics, and computer science, these models provide insight into cellular behavior, responses to stimuli, and complex interactions within biological systems. This article highlights key techniques in computer simulation modeling of cells, such as agent-based modeling, stochastic simulation, and mechanistic modeling. In addition, it explores remarkable advances in the field, including drug discovery, personalized medicine, and the elucidation of basic biological mechanisms. Using computational tools, scientists are pushing the boundaries of cellular research and opening new doors of opportunity for health and scientific discoveries.
Keywords: cell; computer simulation; computer simulation modeling; algorithms